In Situ Formation of Decavanadate-Intercalated Layered Double Hydroxide Films on AA2024 and their Anti-Corrosive Properties when Combined with Hybrid Sol Gel Films - Wu, Junsheng (2018)
A layered double hydroxide (LDH) film was formed in situ on aluminum alloy 2024 through a urea hydrolysis method, and a decavanadate-intercalated LDH (LDH-V) film fabricated through the dip coating method. The microstructural and morphological characteristics were investigated by scanning electron microscopy (SEM). The corrosion-resistant performance was analyzed by electrochemical impedance spectroscopy (EIS), scanning electrochemical microscopy (SECM), and a salt-spray test (SST).The SEM results showed that a complete and defect-free surface was formed on the LDH-VS film. The anticorrosion results revealed that the LDH-VS film had better corrosion-resistant properties than the LDH-S film, especially long-term corrosion resistance. The mechanism of corrosion protection was proposed to consist of the self-healing effect of the decavanadate intercalation and the shielding effect of the sol-gel film.